New fluidic model for in vitro testing of vascular effects of drugs: 4D endothelial sensing (4D-ENDOSENS). (10th June 2022) - Alvarez Castro, E; Carnero, B; Vazquez-Esmoris, I; Almenglo, C; Aymerich, M; Eiras, S; Bao-Varela, C; Gonzalez-Juanatey, JR; Perez-Munuzuri, A; Flores-Arias, MT
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Sociedad Española de Cardiología y Fundación Española del Corazón. Ministerio de Ciencia e innovación (MICINN). España Background: The preclinical in vitro tests of vascular effects are done in cell cultures under static conditions, whereas the in vivo conditions are far from that. So, the effects of blood flow or vessel structure are not considered. This make these models ineffective and unpredictive of the final effects of drugs in vivo, and it is one of the causes for the low rate of success of clinical trials in cardiovascular therapies. Purpose: To elaborate a new preclinical and more realistic model for testing the vascular effects of drugs in a fluidic system with human endothelial cells in a biomimetic structure. Methods: We used laser-based techniques or 3D printing to fabricate a device with the geometries of blood vessels. The fabrication method composed of a two-step technique: 1) a master of the channel was fabricated over soda-lime glass using a laser back-writing technique or over a resin by stereolithographic printing; and 2) the initial master channel was replicated using a soft-lithography method with polidimethylsiloxane (PDMS), that is a biocompatible material with good optical properties. Human umbilical vein endothelial cells (HUVEC) were cultured in the channels walls in order to achieve the most similar device to a human blood vessel. Experimental flux experiments incorporating flow through the channel were performed in order to study cell behaviour in these conditions. Immunocytochemistry and imaging techniques at real-time or as end-point measurement were used to the analysis. Results: Fabrication techniques allowed the free design of the master, so customized structures can be obtained. Fine control of this process allowed tuning the roughness of the channel's surface to enhance the adherence of HUVEC to the final PDMS device. The chemical coating of the inner surface of the channels were optimized in order the endothelial cells support the flow without detaching. The final channels mimicked vessel's anatomy: inner circular section of up to 2 mm of diameter covered with a monolayer of living HUVEC. A planar bifurcation with anatomical structure was used as proof of concept. The model was tested at a range of flow rates (from 0.2 to 10 ml/min) during short and long periods. Blood circulating cells were introduced in the flow to test theit interaction with HUVEC. Cells were stained by immunocytological methods to check their integrity and functionality and the optical quality of the device for imaging purposes. Conclusions: A vessel-on-a-chip for in vitro flow testing on endothelial cells was achieved with differential advantages: customable and accurate design on demand, mimetic anatomical geometries with circular inner cross-section, robust for high flow circulation and good optical properties for imaging analysis. Drug effects on vascular functions like endothelial permeability, inflammatory response or circulating - endothelial cells interaction can be now studied in vitro under flow conditions.